POLITICS OF ISLAMIC LAW IN THE EARLY NEW ORDER ERA (1984 TO 1990) - Rusli Halil Nasution (Proceeding International Seminar of Islamic Studies, 2023)
To make it easier and more systematic to describe the development of Islamic law during the New Order era, the next During the New Order era, the horizontal Latin political tension, between santri and abangan, was fading, or if there was, the tension was below the surface and buried by various daily events, however, this did not mean that political tensions and Islamic struggles just stopped. but the most prominent struggle of this period was more open.The New Order era can be said to be the starting point for the development and more concrete recognition by the state of the existence and enforceability of Islamic law in Indonesia. During the New Order government, several laws and regulations were issued that directly related to the existence of Islamic law in Indonesia, such as Law Number 1 of 1974 concerning Marriage, Government Regulation Number 28 of 1977 concerning Waqf, Law Number 7 of 1989 on Judiciary Religion, and Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law in IndonesiaEven though the position of Islamic law as one of the sources of national law was not very firm in the early days of the New Order, efforts to strengthen it still had to be done. This was shown by KH.M. Dahlan, a minister of religion among NU when he proposed a draft law on Muslim marriage with the support of Islamic factions in the DPR-GR. Despite this failure, this effort was continued by submitting a formal draft law governing judicial institutions in Indonesia in 1970. This effort bore fruit with the issuance of Law No. 14/1970, which recognized the Religious Courts as one of the judicial bodies under the Supreme Court. With this law, according to Hazairin, Islamic law has been applied directly as an independent law.